Erzhi pills ameliorate cognitive dysfunction and alter proteomic hippocampus profiles induced by d-galactose and Aβ1–40 injection in ovariectomized Alzheimer's disease model rats. (1st January 2021) - Xie, Yongyan; Yan, Bo; Hou, Min; Zhou, Maofu; Liu, Chao; Sun, Mengsheng; He, Kun; Fang, Cong; Chen, Yaohui; Huang, Liping
Abstract: Context: Erzhi pills are a classic Chinese medicine prescription, but their effects on Alzheimer's disease (AD) are not clear. Objective: The protective effects of Erzhi pills in AD rats and their potential mechanisms were investigated. Materials and methods: An AD rat model was established by ovariectomy combined with d -galactose and Aβ1-40 injection. Rats were randomly divided into five groups: sham-operated, model, oestradiol valerate (0.80 mg/kg), Erzhi pills high-dose (1.50 g/kg), and Erzhi pills low-dose (0.75 g/kg). Learning and memory abilities were evaluated with the Morris water maze test, oestrogen levels with an ELISA kit, and hippocampal neuron morphology and Nissl bodies in the cytoplasm with H&E and Nissl staining. The expression of ERβ, Aβ1–40, and p-tau 404 was determined by immunohistochemistry. Nano LC-LTQ-Orbitrap Proteomics determined potential targets and related signalling pathways. Western blotting was used to detect the expression of the related proteins. Results: Erzhi pills (1.5, 0.75 g/kg) markedly reduced escape latencies on the MWM, increased numbers of platform crossings, numbers of neurons, Nissl bodies, oestrogen levels (100.18, 43.04 pg/mL), and ERβ-positive cells (57.42, 39.83); Aβ1–40 (18.85, 36.83)- and p-tau 404 (14.42, 29.71)-positive cells were significantly decreased. Proteomics identified more than 100 differentially expressed proteins involved in 48 signalling pathways, five of which are involved in the PI3K/Akt signalling pathway. Western blotting showed decreased expression of GSK3β and Bad, while Akt, PI3K, 14-3-3, Bcl-xl, and Bcl-2 were upregulated. Discussion and conclusion: Erzhi pills may serve as a potential agent for AD therapeutics by improving learning and memory.